1991
DOI: 10.1128/aem.57.7.1956-1962.1991
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory-Based Model of Microbiologically Induced Corrosion of Copper

Abstract: The interactions of bacteria isolated from corroded copper coupons on thin films of copper evaporated onto germanium internal reflection elements were evaluated nondestructively in real time by attentuated total reflectance Fourier transform infrared spectroscopy. The films were stable in the presence of flowing or static sterile culture medium. When exposed to and colonized by the bacterium CCI 8, the copper thin film corroded. Corrosion was enhanced under quiescent conditions. In conjunction with corrosion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…(5AG1), Enterobacter cloacae (17·5FS2) and the Pseudomonadaceae (6FG2) also increased copper levels above the control, but when compared with the sterile control coupon, these increases were not statistically significant. Similar species-specific release of copper by bacteria isolated from corroded copper coupons suspended in municipal wastewater has also been observed by Bremer and Geesey (1991). Edwards et al (1994) suggested that high levels of organic carbon protected copper pipe surfaces from corrosion.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…(5AG1), Enterobacter cloacae (17·5FS2) and the Pseudomonadaceae (6FG2) also increased copper levels above the control, but when compared with the sterile control coupon, these increases were not statistically significant. Similar species-specific release of copper by bacteria isolated from corroded copper coupons suspended in municipal wastewater has also been observed by Bremer and Geesey (1991). Edwards et al (1994) suggested that high levels of organic carbon protected copper pipe surfaces from corrosion.…”
Section: Discussionsupporting
confidence: 69%
“…Keevil (1989) demonstrated the presence of bacterial populations on copper pipe surfaces in cooling towers. Localized corrosion of copper films in freshwater environments has also been shown to be directly attributable to the presence of bacteria (Bremer and Geesey 1991). Furthermore, specific species were shown to increase or decrease corrosion.…”
Section: Introductionmentioning
confidence: 98%
“…posed to play a major role in mature biofilms (Stoodley et al, 2002), type IV pili protein subunits may provide the initial attachment to abiotic surfaces (Figs 2 and 3). Evidence of an initial involvement of protein in biofilm formation on copper surfaces has been reported previously (Bremer and Geesey, 1991). Interestingly, a variety of proteins have the ability to mediate tight interactions with abiotic surfaces, including the Mytilus edulis foot proteins which are capable of mediating interactions with a variety of abiotic surfaces including metals and plastics (Suci and Geesey, 2001).…”
Section: Discussionmentioning
confidence: 83%
“…Garcia et al showed that a mix of seven isolated bacteria can reduce the corrosion of copper pipes [ 93 ]. Another study showed that an isolated bacterium can reduce the corrosion produced by other bacterium [ 94 ], a recent mini-review explains these two roles bacteria can have with respect to corrosion [ 95 ]. Therefore, the study of the reactivity of the biofilm and the interactions of bacteria is a key factor for understanding MIC mechanisms and, as pointed out before, has multiple implications besides the sorption phenomena.…”
Section: Copper Processes In Drinking Water Systemsmentioning
confidence: 99%